Time to occurrence of necrotizing enterocolitis and its predictors among low birth weight neonates admitted at neonatal intensive care unit of felege hiwot compressive specialized hospital BahirDar, Ethiopia, 2021: A retrospective follow-up study - Alene, Tamiru; Feleke, Mulualem Gete; Yeshambel, Addisu; Amare, Abraham Tsedalu; Tigabu, Agimasie; Birlie, Tekalign Amera; Aynalem, Yared Asmare; Kerebeh, Gashaw; Eshetu, Kirubel; Tsega, Tilahun Degu; Wassihun, Biresaw; Adella, Getachew Asmare; et al. (Frontiers in Pediatrics, 2022)
Abstract Background: Globally, the incidence of NEC is varying between 6-15% of all neonates admitted to NICU. Though necrotizing enterocolitis is a multifactorial and life-threatening disease, low birth prematurity is the single cause. Therefore, determining the time to presentation and its predictors of necrotizing enterocolitis were the main goals of this investigation. Methods: An institution-based retrospective follow-up study was conducted among 747 low birth weight neonates admitted to the neonatal intensive care unit of Felege Hiwot comprehensive specialized Hospital from Jaunary1, 2017 to December 30, 2019. The sample size was calculated by using the STATA package. Data were entered into Epi data version 3.1 and exported to STATA version 14 for analysis. The log-rank test and Kaplan Meier were used to display the survival probability and differences between groups. At a significance threshold of 5%, Cox proportional hazard regression was performed to determine the net independent predictors of necrotizing enterocolitis. Result: The overall incidence rate was 0.86 per 1000 person-days (95% CI: 0.67, 1.14) with 6.8% (95% CI: 5.2, 8.9) proportion of necrotizing enterocolitis among low birth weight neonates. Preeclampsia[AHR;1.92(95%,CI:1.03-3.58)] , premature rapture of membrane[AHR; 2.36 (95%, CI: 1.19-4.69)] , perinatal asphyxia [AHR; 4.05 (95%, CI: 2.04-8.60)], gestational age between 28-32 weeks[AHR;3.59 (95%,CI:1.01-8.83)] and birth weigh less than 1000gm [AHR; 5.45 ( 95%,CI:3.84-9.12 ) were the independent predictors of necrotizing enterocolitis. Conclusion: Within the first 1–7 days of a newborn's life, necrotizing enterocolitis was most common. It was discovered that preeclampsia, premature rupture of membrane, perinatal asphyxia, gestational age of 28–32 weeks, and birth weight less than 1000gm were predictors of its occurrence. Keywords: Low birth weight, Necrotizing enterocolitis, Incidence density, Kaplan Meier, BahirDar, Ethiopia